(untitled) (International Journal of Environmental Sciences, 2026)
This study investigates the traditional ecological knowledge (TEK) and conservation of seagrass ecosystems in Barangay Lawigan, City of Mati, Davao Oriental, Philippines. Using a mixed ethnobiological approach, data were collected from 50 purposively selected respondents through interviews, focus group discussions, participant observation, and field validation. The research aimed to document local classifications, uses, and perceptions of seagrass, while assessing how knowledge varies across gender, age, and livelihood groups. Findings show that residents possess extensive knowledge of seagrass ecosystems, highlighting their ecological roles as nursery grounds, sources of food and income, and cultural resources. Five seagrass species were identified, with Enhalus acoroides emerging as the most culturally significant, as reflected by its highest Use Value (UV). High Informant Consensus Factor (ICF) scores indicate strong agreement on the importance of seagrasses for fisheries productivity, coastal protection, and biodiversity support. Despite this, conservation remains limited due to economic vulnerabilities, destructive practices, and weak enforcement of local ordinances. Existing community initiatives, such as coastal clean-ups and Bantay Dagat patrols, are not explicitly targeted at seagrass protection. The results reveal a significant gap between the community’s rich ecological knowledge and the lack of institutional recognition for seagrass conservation. The study highlights the significance of TEK in guiding community-based and policy-aligned seagrass conservation. Integrating TEK into marine spatial planning and institutional frameworks can enhance biodiversity protection, climate resilience, and sustainable coastal livelihood.